Veterinary students' usage and perception of video teaching resources - Roshier, Amanda L.; Foster, Neil; Jones, Michael A. (BioMed Central, 2011)
Background: The purpose of our study was to use a student-centred approach to develop an online video learning resource (called 'Moo Tube') at the School of Veterinary Medicine and Science, University of Nottingham, UK and also to provide guidance for other academics in the School wishing to develop a similar resource in the future.